Optical Testing of Refractive Microlenses - Lindlein, Norbert; et al. (Technisches Messen, 2002)
Microlens testing requires in many cases the measurement of surface deviations and the measurement of the wave aberrations of the lens. The lens function is for the multitude of microlenses brought about through curved surfaces of dielectric substrates. Only GRIN lenses rely on the three-dimensional distribution of the refractive index. For the measurement of the surface deviations the Twyman-Green interferometer and for cylinder lenses the grazing incidence test using diffractive beam splitters are best suited. Wave aberrations should be measured in single pass geometry because of systematic errors in case of big aberrations due to double pass arrangements. Therefore, the Mach-Zehnder on the one hand and the shearing interferometer on the other can be recommended for microlens tests. At the time being also wave front sensor as the Shack-Hartmann test are becoming a suitable alternative to the shearing methods because of its simplicity and sufficient sensitivity. A special field is the test of whole lens arrays. This concerns the paraxial as well as the aberration data. Low aperture lens arrays might be illuminated with plane waves indicating the uniformity of the lens data if a whole field is evaluated simultaneously.
Keywords: Aberrations measurement; Diffractive beam splitters; Interferometry; Microlenses; Wave front sensors